IMPROVING HAMMER THROW TECHNIQUE INSTRUCTION IN UNIVERSITY STUDENTS THROUGH BIOMECHANICAL AND VIDEO-BASED ANALYSIS (International journal of artificial intelligence, 2026)
This study investigates the effectiveness of biomechanical and video-based approaches in improving the methodology of teaching hammer throw technique to university students. Hammer throw is considered one of the most technically complex disciplines in athletics due to its multi-phase rotational movements, high coordination demands, and the necessity of precise force application. Traditional teaching methods often fail to provide sufficient visual and biomechanical understanding of movement execution, which can limit students’ technical development and performance outcomes.